2016
DOI: 10.1017/jfm.2016.699
|View full text |Cite
|
Sign up to set email alerts
|

Velocity statistics inside coherent vortices generated by the inverse cascade of 2-D turbulence

Abstract: We analyze velocity fluctuations inside coherent vortices generated as a result of the inverse cascade in the two-dimensional (2d) turbulence in a finite box. As we demonstrated in [1], the universal velocity profile, established in [2], corresponds to the passive regime of flow fluctuations. The property enables one to calculate correlation functions of the velocity fluctuations in the universal region. We present results of the calculations that demonstrate a non-trivial scaling of the structure function. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The zeroth mode, m = 0, deserves a separate consideration (see also 10,33 ). As was noted before, and can be deduced from the (φ, φ) component of the steady state equation…”
Section: Fluctuationsmentioning
confidence: 99%
“…The zeroth mode, m = 0, deserves a separate consideration (see also 10,33 ). As was noted before, and can be deduced from the (φ, φ) component of the steady state equation…”
Section: Fluctuationsmentioning
confidence: 99%
“…In the same work an interval of separations from the vortex center was found where the flat velocity profile is realized and some theoretical arguments toward the flat profile were formulated. In our paper [20] we demonstrated that the flat profile corresponds to the passive (quasilinear) regime of turbulent fluctuations, and in [21] we calculated the structure function of the velocity fluctuations. In all the works the model of the pumping short correlated in time was used.…”
mentioning
confidence: 90%
“…Therefore a question appears about an internal structure of the vortices. For a short-correlated in time pumping, the problem was investigated in the works [19][20][21]. Let us analyze the structure of the coherent vortex in the static case.…”
mentioning
confidence: 99%
“…The average turbulent energy profile.-Symmetry considerations imply that the magnitude of the diagonal terms of the Reynolds tensor, u 2 and v 2 , as well as the mechanism that dictates them, are different than those for the momentum flux [10,11]. We therefore take a different approach than [17], where the turbulent energy is computed within the same framework used for the momentum flux. Instead, we will show that u 2 and v 2 are determined by the zero modes of the advection equation for two-point correlation functions.…”
mentioning
confidence: 99%